Data-Driven Lead Prioritization in Existing B2B Customer Relationships : A Microfoundations Case Study in a Finnish Digital Mobility Company - Elomaa, Iiro (My University, 2026)
Asiakasdatan merkitys B2B-myynnissä on kasvanut, kun digitaaliset järjestelmät, analytiikka-työkalut ja ennakoivat mallit mahdollistavat asiakkaiden käyttäytymisen tarkemman seuraami-sen. Datavetoiset työkalut voivat auttaa yrityksiä tunnistamaan esimerkiksi aktiivisia, passivoi-tuneita, kasvavia tai asiakkuuden kehittämisen kannalta potentiaalisia asiakkaita. Pelkkä asia-kassignaalien näkyväksi tekeminen ei kuitenkaan vielä selitä, miten myynnin priorisointikäy-tännöt muuttuvat organisaatiossa. Tämän tutkimuksen tarkoituksena on tarkastella, miten datavetoiset työkalut muuttavat ole-massa olevien B2B-asiakkaiden priorisointikäytäntöjä. Tutkimus avaa datavetoisen liidien prio-risoinnin mustaa laatikkoa mikroperustojen näkökulmasta. Mikroperustojen avulla tutkimuk-sessa tarkastellaan, miten yksilöiden tulkinnat, roolien välinen koordinointi ja organisaation rakenteet vaikuttavat siihen, miten dataperusteiset asiakassignaalit muuttuvat käytännön myyntitoiminnaksi. Tutkimus toteutettiin laadullisena tutkimuksena suomalaisessa digitaalisen liikkumisen yrityk-sessä. Ensisijainen aineisto koostuu haastatteluista, joita täydennettiin yrityksen asiakasdataa ja B2B-asiakaskäyttäytymistä kuvaavilla aineistoilla. Tutkimuksen tulokset osoittavat, että da-tavetoiset työkalut eivät muuta priorisointikäytäntöjä suoraan. Ne muuttavat priorisointia epäsuorasti kolmen mekanismin kautta. Ensinnäkin työkalut tekevät olemassa olevia B2B-asiakkaita näkyvämmäksi asiakassignaalien avulla. Toiseksi nämä signaalit täytyy tulkita, arvioi-da ja koordinoida organisaation eri roolien välillä. Kolmanneksi signaalit muuttuvat käytännön toiminnaksi vasta, kun ne kytkeytyvät rutiineihin, vastuisiin, CRM-logiikkaan ja seurantakäy-täntöihin.

The importance of customer data in B2B sales has increased as digital systems, analytics tools, and predictive models enable more detailed monitoring of customer behavior. Data-driven tools can help companies identify, for example, active, inactive, growing, or otherwise poten-tially valuable customers from the perspective of customer development. However, making customer signals visible does not alone explain how sales prioritization practices change within an organization. The purpose of this study is to examine how data-driven tools change prioritization practices for existing B2B customers. The study opens the black box of data-driven lead prioritization from a microfoundations perspective. Through microfoundations, the study examines how individual interpretations, coordination between roles, and organizational structures influence how data-based customer signals are transformed into practical sales action. The study was conducted as a qualitative case study in a Finnish digital mobility company. The primary empirical material consists of interviews, which were supported with company mate-rials describing customer data and B2B customer behavior. The findings show that data-driven tools do not change prioritization practices directly. Instead, they change prioritization indirect-ly through three mechanisms. First, the tools make existing B2B customers more visible through customer signals. Second, these signals must be interpreted, evaluated, and coordi-nated across different organizational roles. Third, signals are transformed into practical action only when they are connected to routines, responsibilities, CRM logic, and follow-up practices.
Keywords: customer relationship management; business-to-business marketing; business-to-business commerce; customership; strategic planning; enterprises; sales work; leadership (activity); fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development